Análisis comparado de la calidad de crónicas deportivas elaboradas por inteligencia artificial y periodistas. - Verdú, Francisco José Murcia; Antón, Rubén Ramos; Rubio, Luis Mauricio Calvo (Revista Latina de Comunicación Social, 2022)
Introduction: In recent years, the presence of artificial intelligence programs in newsrooms has become standardised, which has allowed the writing of texts through algorithms. This research analyses the characteristics of sports chornicles written by artificial intelligence, comparing them with those written by journalists. The aim is to find out whether these types of texts have the same quality standards as those of chronicles written by journalists. Methodology: The methodology used is based on the content analysis of 28 journalistic chronicles, 14 written by journalists and 14 written by artificial intelligence programmes. In all cases, these are sports chronicles on matches corresponding to the Spanish Professional Football League (first and second division). Results: The results show that AIgenerated texts are effective in collecting and ordering data and in reporting game action. However, they lack many of the qualities of a sports chronicle, which are present in texts written by journalists. Conclusions: The chronicles produced by artificial intelligence do not represent a quality contribution to the journalistic genre, lacking analytical or interpretative character, in both cases qualities traditionally present in sports journalism.